Reactive power coordinated optimisation method with renewable distributed generation based on improved harmony search - Sheng, Wanxing; Liu, Ke-yan; Liu, Yongmei; Ye, Xueshun; He, Kaiyuan (IET generation, transmission & distribution, 2016)
The reactive power coordinated optimisation problem for distribution network (DN) with the integration of renewable distributed generation (DG) is investigated in this study. By actively participating in reactive power control together with an under-load tap changer and shunt capacitors, DG can operate more effectively in the DN. Non-dispatchable DG is considered in the coordinated optimisation method. The objective of the proposed reactive power coordinated optimisation method is to minimise active power loss and to decrease the number of switching device operations while maintaining the grid voltage within the allowable range. The optimisation problem is to solve a variable combination including integers and continuous variables, which will formulate a mixed integer non-linear programming (MINLP) problem. The control variable includes operations of traditional reactive power control devices and the reactive power adjustments of DGs. To solve the MINLP problem, a heuristic searching method, an improved harmony search algorithm is proposed with adaptive parameters process. Numerical tests on a standard 10-kV distribution system and a real distribution system demonstrate the applicability of the proposed reactive power coordinated optimisation method.